Conflict Management Styles Among Public Sector Managers in Malaysia. - Suppiah, Waitchalla Rrv (2007)
This study examined the competence-based approach to conflict management from the Malaysian perspective especially on the effectiveness and appropriateness of the conflict management styles as perceived by dyads of superiors-subordinates. In the process, this study set out to determine the conflict management styles used by Administrative and Diplomatic Services (ADS) officers in handling interpersonal conflicts with their subordinates. In addition, it looked at the moderating effects of individual attribute, professional profile and management styles on the effectiveness and appropriateness of the conflict management styles used as reported by the superiors and subordinates. Self-administered questionnaires were used to gather data. The sample consisted of 383 dyads of superiors-subordinates selected randomly from the 28 Ministries/Department. The quantitative data were analysed using various statistical and exploratory data analysis methods, descriptive tests, ANOVAs, Chi-square test of independence, and MANOVA.The findings indicated that ADS officers used integrating, compromising and dominating styles to handle interpersonal conflicts with their subordinates. The least used style was the obliging style. The 9,9 management style was the most frequently used style followed by 1,9 management style. The least used style was the 1 ,I management style. Both the superiors and subordinates rated the integrating style as the most effective, most relationally appropriate and most situationally appropriate style. The obliging style was rated as the least effective and least situationally appropriate style by both the superiors and subordinates while the dominating style was reported as the least relationally appropriate. The findings revealed that the subordinates were relatively satisfied with the level of supervision. However, there were no significant findings on the moderating effects of individual attribute, professional profile and management styles on the effectiveness and appropriateness of the conflict management styles used as reported by superiors and subordinates. Further research was recommended, in particular on the competence-based approach to conflict management involving a social setting within an Eastern environment.